Theory of Regular Economies. - Nagata, Ryo (Series on Mathematical Economics & Game Theory., 2004)
This book presents a comprehensive treatment of the theory of regular economies, which is one of the most advanced topics in modern general equilibrium theory, emphasizing the basic ideas, the tools and the important applications. Although many notions and tools of differential topology are required to understand the theory, the author chooses a minimum of them and heuristically arranges them; that is, instead of lumping together all the necessary mathematics, the author puts at the beginning of each chapter the minimum mathematics required for the economic analysis of the chapter, so that the.